High‐Efficiency Ion‐Exchange Doping of Conducting Polymers - Jacobs, Ian E.; Lin, Yue; Huang, Yuxuan; Ren, Xinglong; Simatos, Dimitrios; Chen, Chen; Tjhe, Dion; Statz, Martin; Lai, Lianglun; Finn, Peter A.; Neal, William G.; D'Avino, Gabriele; et al. (Advanced materials (Weinheim), 2022)
Molecular doping—the use of redox‐active small molecules as dopants for organic semiconductors—has seen a surge in research interest driven by emerging applications in sensing, bioelectronics, and thermoelectrics. However, molecular doping carries with it several intrinsic problems stemming directly from the redox‐active character of these materials. A recent breakthrough was a doping technique based on ion‐exchange, which separates the redox and charge compensation steps of the doping process. Here, the equilibrium and kinetics of ion exchange doping in a model system, poly(2,5‐bis(3‐alkylthiophen‐2‐yl)thieno(3,2‐b)thiophene) (PBTTT) doped with FeCl3 and an ionic liquid, is studied, reaching conductivities in excess of 1000 S cm−1 and ion exchange efficiencies above 99%. Several factors that enable such high performance, including the choice of acetonitrile as the doping solvent, which largely eliminates electrolyte association effects and dramatically increases the doping strength of FeCl3, are demonstrated. In this high ion exchange efficiency regime, a simple connection between electrochemical doping and ion exchange is illustrated, and it is shown that the performance and stability of highly doped PBTTT is ultimately limited by intrinsically poor stability at high redox potential. An extremely efficient ion‐exchange doping process for conjugated polymers which enables conductivities exceeding 1000 S cm−1 is demonstrated. Factors which affect ion exchange, such as electrolyte concentration, doping solvent, and film crystallinity are discussed. When exchange is efficient there is a direct correspondence between ion exchange electrochemical doping, which is used to reveal the detrimental impact of off‐target oxidation reactions.